HUBUNGAN PERSEPSI TERHADAP METODE PEMBELAJARAN DARING DENGAN MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI SISTEM INFORMASI-UKSW - Prisilia Tehupuring; Adriyanto J Gundo (Program Studi PGSD Universitas Flores, 2022)
The purpose of this study is to knowing and explaining the influence of the SWCU Salatiga information system student's perception of online learning methods on learning motivation during the Covid-19 pandemic. This type of research is descriptive quantitative. The research subjects used were Satya Wacana Christian University SI (Information System) active students, especially the 2019 and 2020 batches. The data collection technique of this research uses a questionnaire through the Google-Form media. The data that has been collected is then analyzed using univariate analysis techniques and bivariate analysis through the help of SPPS Version 20.0. The result of the study is that there is a relationship between student’s perceptions and learning motivation towards the online learning method of the 2019 and 2020 SWCU Information Systems Study Program during the Covid-19 pandemic.